Dealing with critical challenges in African innovation platforms: Lessons for facilitation - Swaans, Cornelis P.M.; Cullen, Beth; Rooyen, Andre F. van; Adekunle, A.A.; Ngwenya, H.; Lema, Zelalem; Nederlof, S. (2013)
Innovation platforms are increasingly used by research and development initiatives to actively engage the poor in agricultural innovation processes. These platforms are forums for action and learning, where different types of actors come together to address issues of mutual concern. However, the dynamic nature of the innovation process, and the differences in interest, capacity and power among the actors involved, pose a challenge in the facilitation of these platforms. We believe that the key to success is very much linked to the attitude, skills and capacities of the innovation broker. This paper highlights seven key issues which in our view are critical to effective platform facilitation and have not received the attention they deserve: the dynamic and evolving nature of platforms; power dynamics; gender equity; external versus internal facilitation; sustainability of the process; issues of scale; and monitoring and evaluation. These issues and implications for facilitation of innovation platforms will be discussed based on examples from the field and in relation to current theories.